DEVICE OF ULTRASONIC ATOMIZATION, THE AEROSOL - Tatiana Ivanovna Drovosekova; Sergey Borisovic Sizov; Natalia Sergeevn Strigun (Современная наука и инновации, 2022)
Today, nebulazers are used to prevent and treat diseases of the respiratory system organs. Nebulazer is an apparatus that converts a liquid medication into an aerosol for inhalation, selectively acting on certain parts of the respiratory tract.